2009
DOI: 10.1007/s12528-009-9021-8
|View full text |Cite
|
Sign up to set email alerts
|

Technology’s effect on achievement in higher education: a Stage I meta-analysis of classroom applications

Abstract: This paper reports the findings of a Stage I meta-analysis exploring the achievement effects of computer-based technology use in higher education classrooms (non-distance education). An extensive literature search revealed more than 6,000 potentially relevant primary empirical studies. Analysis of a representative sample of 231 studies (k = 310) yielded a weighted average effect size of 0.28 surrounded by wide variability. A mixed effects model was adopted to explore coded moderators of effect size. Research d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 21 publications
5
45
0
4
Order By: Relevance
“…This outcome is consistent with numerous studies which report that despite widespread access and possible learning advantages (e.g., Blok, Oostdam, Otter, & Overmaat, 2002;Mayer, Mautone, & Protehro, 2002), computer technology remains under-utilized in education and the potential of computer technology is not being realized (Abrami, 2001;Mueller, 2009;Muir-Herzig, 2004). A recent meta-analysis of technology's impact on student achievement in higher education (Schmid, et al,., 2009) suggests that although technology has demonstrated medium positive effect sizes on learning outcomes, highest levels of technology saturation were related with negative effects. There are clearly additional variables beyond access and use that impact learning outcomes with technology that need to be addressed.…”
Section: Uses Of the Blackberry ® Devicesupporting
confidence: 83%
“…This outcome is consistent with numerous studies which report that despite widespread access and possible learning advantages (e.g., Blok, Oostdam, Otter, & Overmaat, 2002;Mayer, Mautone, & Protehro, 2002), computer technology remains under-utilized in education and the potential of computer technology is not being realized (Abrami, 2001;Mueller, 2009;Muir-Herzig, 2004). A recent meta-analysis of technology's impact on student achievement in higher education (Schmid, et al,., 2009) suggests that although technology has demonstrated medium positive effect sizes on learning outcomes, highest levels of technology saturation were related with negative effects. There are clearly additional variables beyond access and use that impact learning outcomes with technology that need to be addressed.…”
Section: Uses Of the Blackberry ® Devicesupporting
confidence: 83%
“…Chandra and Loyd (2008) have shown that e-learning in secondary schools can improve student performance for some scholars, but reduce it for others. In higher education, Schmid et al (2009) calculated that using ICT during teaching had a positive influence on the achievement of students, although they stress that ICT-supported teaching also needs good instructional design and teaching practices.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly there is much international research which supports the assumption that the use of technology within the educational setting has a positive influence on learning, especially in improving cognition (Kozma, 1994(Kozma, , 2003Schmid et al, 2009;Tamim, Bernard, Borokhovski, Abrami, & Schmid, 2011), but also those who question such conclusions (Clark, 1994;Livingstone, 2012;Means, Toyama, Murphy, Bakia, & Jones, 2009). While recognizing the inevitability of technology's presence in higher education in the UAE however, there is wide acknowledgement that the integration of technology into teaching and learning should be pedagogically driven, and to be effective, requires "teacher training, curriculum structures and materials, classroom practices and modes of assessment [to be] redesigned at all levels" (Livingstone, 2012, p. 10).…”
Section: Training In Tertiary Educationmentioning
confidence: 99%